Ikonográfia – korszakok lenyomata és tükre: Az ókeresztény ikonográfia néhány képtípúsának elemzése - Újvári, Edit (Per Aspera ad Astra, 2019)
This paper focuses on the specifics of the iconographic research, also describing the history of this discipline. The visual representations – paintings, sculptures, carvings – have a very important role in every historical era, and they express ideological thoughts, contents and meanings. All these are interpreted by iconographic research, with defining and specifying of the topics and attributes of the image types and analysing of the compositions. The theoretical, historical and critical approaches are complemented by the analysis of some typical early Christian iconographic types, Greco-Roman mythological figures in Christian context and the Traditio legis (“the Giving of the Law”) image type.